Analisis Strategis Pengembangan Voltwave Network Ev-Station Sebagai Solusi Infrastruktur Pengisian Kendaraan Listrik di Indonesia - Anggriwan, Phellano; Indradewa, Rhian; Negoro, Dimas Angga; Iskandar, Muhammad Dhafi (Syntax Literate, 2025)
VoltWave Network EV Station is a business initiative designed to respond to the rapid growth of Indonesia’s electric vehicle (EV) industry. The project focuses on developing and operating Public Electric Vehicle Charging Stations (SPKLU) with an integrated service concept emphasizing premium customer experience. Beyond providing charging infrastructure, VoltWave adds value through supporting facilities such as modern waiting lounges, food courts, robotic carwashes, workspaces, and high-speed Wi-Fi connectivity. This study employs a strategic analysis method, including external analysis (Porter’s Five Forces, PESTEL), internal analysis (RBV, VRIO), and financial feasibility assessments (NPV, IRR, ROI, Payback Period). The results show that Indonesia’s EV industry has significant growth potential, supported by strong government policies. Strategically, VoltWave is positioned in the “grow and build” quadrant, focusing on expanding into industrial and urban areas. Financially, the project is feasible, yielding a positive NPV, an IRR above loan interest rates, and a payback period of 4.8 years. With its service differentiation and comprehensive risk management, VoltWave presents a promising solution for advancing Indonesia’s electric vehicle charging infrastructure.